Programme And Model For Institutional Development of Tobacco Area Based On Farmer Corporation In East Java - R. Achmad Djazuli; Mahrus Ali; Yeni Ika Pratiwi; Garist Sekar Tanjung (Agricultural Science, 2021)
Tobacco as one of the plantation crop commodities can contribute to state income, but on the other hand there are many things that become obstacles for farmers in increasing production and business income, there is no government support in controlling tobacco marketing patterns, there is no cooperative relationship between farmers and tobacco companies that mutual benefits, as well as some problems in tobacco farmer institutions. Research purposes To find out the current condition of East Java tobacco farmers, model for the tobacco area based on farmers' corporations in East Java and program in realizing a model for developing tobacco plantation areas based on smallholder corporations in East Java. The research objectives are: (1) to determine the current condition of tobacco farmers in East Java, (2) to develop an institutional model for tobacco plantations based on farmers' corporations, and (3) to develop programs to realize a model for developing tobacco plantation areas based on farmers' corporations. The data analysis method used in this study is trend analysis, description analysis. Research Results: Program implementation requires coordination and cooperation of various parties related to tobacco. Furthermore, at each stage of implementation, it is necessary to carry out periodic evaluations to find out the shortcomings so that adjustments and improvements can be made at the next stage and it is necessary to follow the rules that have been agreed upon in the memorandum of agreement.